Estimating a stylized fiscal policy DSGE model for Brazil - Rodrigo Mendes Pereira (Institute for Applied Economic Research (ipea), 2019)
This paper builds a small size dynamic stochastic general equilibrium (DSGE) model with government, aiming to replicate key features of the Brazilian economy. I first calibrate and then I use Bayesian methods to estimate the model for Brazil, with 20 years of quarterly aggregate data. Contrary to the conventional knowledge, I find mixed evidence on the pro-cyclicality of the fiscal policy in Brazil. Moreover, the results suggest that tax rate changes have been used to counter changes in the level of government indebtedness, however in a small degree if compared to other international evidence.
Keywords: 330; DSGE model; fiscal policy; bayesian estimation